Upaya Guru dalam Meningkatkan Motivasi Belajar Siswa di MI Islamiyah Pucangtelu Lamongan - Ma’rufah, Zayyin Kholishotul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to identify the teacher's efforts in motivating students at Madrasah Ibtidaiyah Islamiyah Pucangtelu Lamongan. Student learning problems are still very small, because many students are less interested in learning. This has an impact on increasing students' learning, starting from an environment that involves a lack of parental attention in student learning. Find out the location at MI Islamiyah Pucangtelu School Lamongan Jl. Located in. Santoso Pillar. This study uses qualitative methods to build documents based on the results of interviews, observations, and documentation. This is analyzed through document reduction, document presentation, and conclusions. The results of this study indicate that students' learning motivation is still lacking, so the teacher tries to motivate students to learn by providing strategies, methods, rewards and punishments. Facility B which supports the next learning process while the supporters are learning motivation factors. High interest in praise, gifts, rewards, and learning. Barriers to students' background due to family problems, poor moral conditions, inadequate relationships, and low interest in learning.